The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.athoracsur.2018.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Handoffs From the Operating Room to the Intensive Care Unit After Cardiothoracic Surgery: From The Society of Thoracic Surgeons Workforce on Critical Care

Abstract: This document has been approved by The Society of Thoracic Surgeons Executive Committee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…An integral component of these practice bundles includes preoperative and postoperative nutrition strategies developed to optimize the nutritional status of cardiac surgery patients with nutritional risk. 5,8,9 An inadequate or delayed initiation of nutritional support after surgery may aggravate preexisting malnutrition of cardiac surgery patients. Therefore, there is an urgent need to systematically identify malnourished patients who would most likely benefit from early initiated intense perioperative nutrition support.…”
Section: Perioperative Care: Cardiac Surgery Patients Need Nutrition mentioning
confidence: 99%
“…An integral component of these practice bundles includes preoperative and postoperative nutrition strategies developed to optimize the nutritional status of cardiac surgery patients with nutritional risk. 5,8,9 An inadequate or delayed initiation of nutritional support after surgery may aggravate preexisting malnutrition of cardiac surgery patients. Therefore, there is an urgent need to systematically identify malnourished patients who would most likely benefit from early initiated intense perioperative nutrition support.…”
Section: Perioperative Care: Cardiac Surgery Patients Need Nutrition mentioning
confidence: 99%
“…The overall analysis using the REM revealed that there was a notable difference between the experimental group and the baseline, with Z=7.62, RR =0.33, and 95% CI: 0.24 to 0.43. After CTS, there were 72.46% of critical patients with grade I and II cardiac function, lower than 87.49% reported by Chatterjee et al [2019] (16).…”
Section: Discussionmentioning
confidence: 62%
“…After the procedure is completed during the recovery period, clear communication between the surgical, anesthesia, critical care and nursing teams are vital (5). Communication should focus on the extent of stent graft coverage, hemodynamic disturbances, airway or pulmonary concerns, whether planned or unplanned concomitant procedures were performed, anatomical concerns for malperfusion, whether femoral closure devices were deployed and distal pulse examination.…”
Section: Preoperative Considerationsmentioning
confidence: 99%